Artists' interviews and their use in conservation: reflections on issues and practices. Issue 2 (2nd July 2016) - Cotte, Sabine; Tse, Nicole; Inglis, Alison
Abstract : Artists' interviews are widely used in the conservation of contemporary art. Best practice is detailed in recent publications, conferences and workshops, however, there is little information on how to analyse the data collected, and the issues related to the dissemination and future access to the content. This article examines various techniques of analysis appropriated from qualitative research in the social sciences, and relates them to the intended uses of interviews in conservation. Drawing on a case study that involved interaction with an artist over several years, including interviews and informal conversations, this article argues that a conservators' specific skills set has the capacity to interpret the findings and to understand the creative processes. It also highlights the importance of reflexivity and the public circulation of this interpretation, which is essential for the development of a sustainable practice of artists' interviews in conservation.